Color Stability of Three Composite Resins following Accelerated Artificial Aging: An In-Vitro Study - Haleh Heshmat; Maryam Hoorizad Gangkar; Mansoreh Emami Arjomand; Mohammad javad Kharazifard (Islamic Dental Association of Iran, 2014)
Background and Aim : Discoloration is among the most common problems of composite restorations. Color change over time compromises the main advantage of composite resins namely their high esthetics. In such cases, the restoration needs to be replaced. .The aim of this in-vitro study was to evaluate the effect of accelerated artificial aging (AAA) on the color stability of three composite resins (Filtek Z250, Filtek Z250XT, and Filtek Supreme).  Materials and Methods : In this experimental study, 7 composite specimens with equal dimensions were fabricated of each composite resin. The initial color of specimens was measured using a spectroradiometer according to the CIE L*a*b* system. The specimens were then submitted to AAA for 384h and underwent color assessment again. Before and after aging, the surface roughness of one specimen from each group was determined by Atomic Force Microscopy (AFM) . The obtained color parameters were analyzed by one-way ANOVA and Tukey's test. Results: The color change of Filtek Z250 was significantly lower than that of Filtek Z250XT and Filtek Supreme (P≤0.05). No statistically significant differences were found between Z250XT and Supreme in this respect (P>0.05 ).  Conclusion : All composite resins showed color change above the clinically acceptable threshold . Z250 microhybrid composite was more color stable than nano-composites (Z250XT and Supreme). AAA increased the surface roughness in all groups but it was within the clinically acceptable range .